2022
DOI: 10.52998/trjmms.1069268
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Port State Control on Turkish Flagged Ships Through the Association Rule Mining

Abstract: Ship inspections are one of the best ways of improving safety at sea. Therefore, it is vital to determine the parameters that cause deficiencies in the prevention of ship accidents. The main purpose of this study is to analyze the inspection results of Turkish flagged ships using the data mining model. Considering a total of 209 inspection reports resulting in the detention of Turkish flagged ships between 2014 and 2019, the Apriori Algorithm was applied using SPSS Modeler 18.0 software to determine the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Wang et al (2021) found that the biggest deficiencies in ship detentions during Tokyo MoU PSC inspections were caused by fire safety and navigational safety, using a Bayesian network model. Yang In addition, data mining (Tsou, 2019;Xiao et al, 2021;Sevgili & Töz, 2022) and statistical analysis studies (Arslan & Eyigün, 2016;Farag, 2016;Bolat, 2019;Ukić Boljat et al, 2020;Mantoju, 2021;Prieto et al, 2021;Şanlıer, 2020Kostović, et al, 2022, Turna & Öztürk, 2023Uçar & Boran, 2023) have also been carried out. Tsou (2019) There are also studies on the legal dimension of port state control (Keselj, 1999;Stoyanov & Terlemesian, 2004;Bang & Jang, 2012; and studies on stakeholders (Piniella et al, 2020;Nwokedi et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al (2021) found that the biggest deficiencies in ship detentions during Tokyo MoU PSC inspections were caused by fire safety and navigational safety, using a Bayesian network model. Yang In addition, data mining (Tsou, 2019;Xiao et al, 2021;Sevgili & Töz, 2022) and statistical analysis studies (Arslan & Eyigün, 2016;Farag, 2016;Bolat, 2019;Ukić Boljat et al, 2020;Mantoju, 2021;Prieto et al, 2021;Şanlıer, 2020Kostović, et al, 2022, Turna & Öztürk, 2023Uçar & Boran, 2023) have also been carried out. Tsou (2019) There are also studies on the legal dimension of port state control (Keselj, 1999;Stoyanov & Terlemesian, 2004;Bang & Jang, 2012; and studies on stakeholders (Piniella et al, 2020;Nwokedi et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been studies on the analysis of the status of the Turkish flag in the MoUs (Bolat, 2019;Yılmaz, 2020;Uygur & Bolat, 2021;Sevgili & Töz, 2022;Kan, 2023), and some studies on the Black Sea and Mediterranean MoUs (Emecen Kara, 2016;Şanlıer, 2020;Akpınar & Şahin, 2020;Maşalacı & Çakır, 2023;Uçar & Boran, 2023). Looking at studies on Turkish flag ships, Bolat (2019) deficiencies were identified especially in the areas of navigational safety, fire safety and life-saving equipment of Turkish flagged ships, throughout the inspections of Tokyo MoU.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation